Overall survival indirect treatment comparison between brigatinib and alectinib for the treatment of front-line anaplastic lymphoma kinase–positive non–small cell lung cancer using data from ALEX and final results from ALTA-1L. (2nd September 2022) - Reckamp, Karen L.; Lin, Huamao M.; Cranmer, Holly; Wu, Yanyu; Zhang, Pingkuan; Kay, Stephen; Walton, Laura J.; Shen, Junwu; Popat, Sanjay; Camidge, D. Ross
Abstract: Background: Second-generation anaplastic lymphoma kinase ( ALK) gene targeted tyrosine kinase inhibitors (TKIs) alectinib and brigatinib have shown efficacy as front-line treatments for ALK -positive non–small cell lung cancer (NSCLC). No head-to-head data are currently available for brigatinib vs alectinib in the ALK-TKI–naive population. Objective: To estimate the relative overall survival (OS) for brigatinib vs alectinib with indirect treatment comparisons (ITCs) using ALEX and ALTA-1L clinical trial data. Methods: The latest aggregate data from the ALEX trial and final patient-level data from ALTA-1L were used. ITCs were conducted with/without treatment crossover adjustments to estimate relative OS. Bucher methods, anchored matching-adjusted indirect comparisons (MAICs) and unanchored MAICs were employed in ITCs without treatment crossover adjustments. An inverse probability of censoring weight Cox model, a marginal structure model and rank-preserving structural failure time models (with/without re-censoring) within an anchored MAIC were used in ITCs with treatment crossover adjustments. Hazard ratios (HRs) and 95% confidence intervals (CIs) were reported. Results: HRs for brigatinib vs alectinib for relative OS generated from ITCs without treatment crossover adjustments ranged from 0.90 (95% CI: 0.59–1.38) in the unanchored MAIC to 1.20 (95% CI: 0.69–2.11) using the Bucher method. Methods employing treatment switching adjustments estimated HRs for relative OS ranging from 0.74 (95% CI: 0.38–1.45) to 1.11 (95% CI: 0.63–1.94). Results from all ITCs did not indicate statistically different survival profiles. Conclusion: Regardless of ITC methodology, OS is comparable for brigatinib vs alectinib in patients with ALK + NSCLC previously untreated with an ALK inhibitor.